The Role of Listening to Music as Self Healing in Reducing Stress in Covid-19 Survivor in Surabaya - Dhamoo Aldamma Firmansyah; Lucky Abrorry (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA BLITAR, 2023)
The condition of pandemics Covid-19 has caused many people to be susceptible to stress, one way to lower stress is by listening to music. This study aims to know whether there is a role of listening to music as a form of self-healing for stress reduction on Covid-19 survivors in Surabaya. This study is conducted using the explorative descriptive method. The population of this research is 51.571 Covid-19 survivors in Surabaya, while the sample chosen is 144. The sampling method used in this study is the purposive sampling technique, while the measuring of listening to music uses its own scale. This study is using cross-tabulation of descriptive data for analysis. The research results show that listening to music is considered effective in lowering stress among covid-19 survivors. The result categories are 66.7% considered effective, 21.5% considered very effective, 9.7% considered less effective, and 2.1% considered ineffective.